2021
DOI: 10.2147/cmar.s315379
|View full text |Cite
|
Sign up to set email alerts
|

No Detection of Pseudocapsule of Tumor-Parenchyma Interface on Multidetector Computed Tomography (MDCT) Images: Clinical Significance and Histological Reflections in Renal Cell Carcinoma

Abstract: Pseudocapsule (PS) of tumor-parenchyma interface (TPI) can be detected by MDCT (ctPS) in renal cell carcinoma (RCC) with exceptions. We aim to study the prognostic implications and histological reflections of no detection of ctPS in RCC. Patients and Methods: A total of 210 RCC patients who had MDCT examination and received nephrectomy in our institution were included in the analysis. Absence or presence of ctPS was recognized, and its associations with overall survival (OS) and progression-free survival (PFS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Author details 1 Department of Urology, Seoul National University Hospital, 101 Daehak-Ro, Jongno-Gu, Seoul 03080, Korea. 2 Department of Urology, Seoul National University College of Medicine, Seoul, South Korea.…”
Section: Abbreviationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Author details 1 Department of Urology, Seoul National University Hospital, 101 Daehak-Ro, Jongno-Gu, Seoul 03080, Korea. 2 Department of Urology, Seoul National University College of Medicine, Seoul, South Korea.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) incidence is increasing [ 1 ], but a clinical hurdle regarding its treatment exists owing to its heterogeneous clinical characteristics, leading to variable patient survival outcomes [ 2 ]. Although TNM stage and Fuhrman nuclear grade are well-known strong independent prognostic factors after RCC surgical treatment [ 3 , 4 ], current classifications cannot perfectly stratify risk levels [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolonging the survival time of patients with advanced renal cell carcinoma is the focus of clinical research. However, no optimum remedies for renal cancer have been found at present, and some studies have shown that traditional Chinese medicine (TCM) has unique advantages in the treatment of malignant urinary tumors [ 8 10 ]. Since renal cancer is an immune-related malignant tumor, the application of TCM treatment based on the concept of holistic treatment and syndrome differentiation is beneficial to improve the body tolerance of patients and control the progression of renal cancer.…”
Section: Introductionmentioning
confidence: 99%